A brief natural history of the orgasm. Issue 1 (1st January 2020) - Lodé, Thierry
Abstract : Why the sexual climax, in humans, results in a pleasurable experience remains an important biological question. Analysis of evolutionary traits in numerous Vertebrates suggests that orgasm evolved through three phylogenetic stages during the transition from external to internal fertilization and viviparity. First, orgasm is directly dependent on ejaculation in males and the expulsion of fluids from the ovarian and urethral glands (Skene's) in females. I propose that sexual orgasm could come from the primitive reflex of discharging gametes to ensure reproduction. Thus, the understanding of orgasm should not be reduced to a penis- or a clitoris-centred paradigm. Secondly, orgasm has evolved to stimulate sexual activity because the evolutionary transition from external fertilization to internal fertilization has been accompanied in numerous species with a lessening in reproductive rates. Because sexual activity encourages reproduction, it can be argued that orgasm has evolved to increase sexual activity, particularly in viviparous species with low reproductive rates. Third, internal fertilization in the genital tract of females weakens the visibility of the putative success of fertilization. Female sexual fluids and proteins can bias fertilization in favour of preferred males. Because orgasm could promote a better choice of partner, I argue that female orgasm may have evolved as a post-copulatory selection tactic by which females can increase their control of mates.